Engineering regioselectivity in the hydrosilylation of alkynes using heterobimetallic dual-functional hybrid catalysts. Issue 1 (19th November 2021) - Roemer, Max; Keaveney, Sinead T.; Gonçales, Vinicius R.; Lian, Jiaxin; Downes, James E.; Gautam, Shreedhar; Gooding, J. Justin; Messerle, Barbara A.
Abstract : The synthesis and characterization of carbon black supported rhodium and iridium heterobimetallic hybrid catalysts and their application in the hydrosilylation of alkynes is described. Abstract : The synthesis and characterization of carbon black supported rhodium and iridium heterobimetallic catalysts, termed hybrid catalysts, and their application in the hydrosilylation of alkynes is described. An aryl diazonium grafting procedure was applied to simultaneously immobilize Rh and Ir pyrazole–triazole complexes with tethers of varying lengths to carbon black, yielding the hybrid catalysts. The complexes differ in metal centre oxidation state and co-ligands, which are CO or Cp*Cl for the Rh complexes and Cp*Cl for the Ir complexes. The immobilization results in simultaneous surface binding and modification of the Rh complexes bearing CO-ligands. In this process, the CO ligands are removed and the overall structure of the catalytically active complex is altered. Analysis of the hybrid catalysts by XPS and SEM/EDX shows that the catalysts bear both surface bound Rh- and Ir-complexes. The Rh content is substantially higher than the Ir content. This is due to more efficient binding of the modified Rh complexes to the carbon black, as they feature two potential binding sites. Synchrotron based X-ray absorption spectroscopy (XAS) at the Rh K- and Ir L3 edges further confirms the presence of the surface bound metal complexes. There is no indication that the presence of a secondary metal affects the electronic structure of the adjacent metal in the systems under investigation, for either the long or short tether derivatives. The performance of the different catalysts was assessed for promoting the hydrosilylation of alkynes, an important industrially relevant reaction. All catalysts are highly efficient. The modified Rh sites are α-selective in the product formation on activation of terminal alkynes, while the RhCp*Cl and IrCp*Cl sites are β( Z )-selective. When operating at mild conditions with high metal loadings, the surface bound Rh catalyst is the active species, while the Ir sites are inactive. At a lower overall surface coverage or higher temperature, the Ir sites become active, which allows engineering of the regioselectivity by adjusting surface coverages and metal loadings.